Impact of pretreatment dihydropyrimidine dehydrogenase genotype‐guided fluoropyrimidine dosing on chemotherapy associated adverse events. Issue 4 (23rd February 2021) - Wigle, Theodore J.; Povitz, Brandi L.; Medwid, Samantha; Teft, Wendy A.; Legan, Robin M.; Lenehan, John; Nevison, Stephanie; Panuganty, Veera; Keller, Denise; Mailloux, Jaymie; Siebring, Victoria; Sarma, Sisira; et al.
Abstract: Consensus guidelines exist for genotype‐guided fluoropyrimidine dosing based on variation in the gene dihydropyrimidine dehydrogenase ( DPYD ). However, these guidelines have not been widely implemented in North America and most studies of pretreatment DPYD screening have been conducted in Europe. Given regional differences in treatment practices and rates of adverse events (AEs), we investigated the impact of pretreatment DPYD genotyping on AEs in a Canadian context. Patients referred for DPYD genotyping prior to fluoropyrimidine treatment were enrolled from December 2013 through November 2019 and followed until completion of fluoropyrimidine treatment. Patients were genotyped for DPYD c.1905+1G>A, c.2846A>T, c.1679T>G, and c.1236G>A. Genotype‐guided dosing recommendations were informed by Clinical Pharmacogenetics Implementation Consortium guidelines. The primary outcome was the proportion of patients who experienced a severe fluoropyrimidine‐related AE (grade ≥3, Common Terminology Criteria for Adverse Events version 5.0). Secondary outcomes included early severe AEs, severe AEs by toxicity category, discontinuation of fluoropyrimidine treatment due to AEs, and fluoropyrimidine‐related death. Among 1394 patients, mean (SD) age was 64 (12) years, 764 (54.8%) were men, and 47 (3.4%) were DPYD variant carriers treated with dose reduction. Eleven variant carriers (23%) and 418 (31.0%) noncarriers experienced a severe fluoropyrimidine‐related AE ( p  = 0.265). Six carriers (15%) and 284 noncarriers (21.1%) experienced early severe fluoropyrimidine‐related AEs ( p  = 0.167). DPYD variant carriers treated with genotype‐guided dosing did not experience an increased risk for severe AEs. Our data support a role for DPYD genotyping in the use of fluoropyrimidines in North America.